THE EFFECT OF CEO CHARACTERISTICS ON PRE-EARNINGS MANAGEMENT PROFITABILITY - Putra, Adhitya Agri (Jurnal Akuntansi dan Keuangan Indonesia, 2021)
This research aims to examine the effect of CEO characteristics on pre-earnings management profitability. CEO characteristics include gender, tenure, age, education level, founding-family status, and nationality. Pre-earnings management profitability is measured by return on assets minus discretionary accruals. Data analysis uses firm and year fixed-effect regression analysis. The result shows that female CEO, longer tenure CEO, CEO with higher education levels, and foreign CEO increase firms' profitability without engaging in earnings management. On the other hand, there is no effect of CEO age and founding-family status on pre-earnings management profitability. This research contributes to filling the gap of inconsistent previous findings of CEO characteristics and profitability by considering earnings management behavior.